Os usos do processo de impeachment do presidente da república sob a égide constituição de 1988 e da lei federal n. 1.079/50 - Medeiros Júnior, Roberto Batista de (Universidade Federal Rural do Semi-Árido, 2018)
The present thesis presents scope in the analysis of the institute of the impeachment in the country order, through the revisiting of its origin, its political and juridical unfoldings in the historical experience. With the purpose of deepening this investigation, it was proposed the analysis of the legislation that foresees the impeachment and the crimes of responsibility, their origin, as well as their uses throughout the decades in which it is validity, revisiting the origin of laws previous to her that they were the same institute. By means of a deductive hypothetical method, inherent to the discussion, it was concluded that impeachment in the executed forms is incompatible with the presidential system of government, approaching the parliamentary molds, and that its popularization, as well as its successive uses, has favored a banalization of the an institute that should be used with parsimony and conscience.
Monografia
Keywords: Impeachmen; Presidencialismo; Crime de responsabilidade; Impeachment; Presidentialism; Responsibility crime; CIENCIAS SOCIAIS APLICADAS::DIREITO